2001
DOI: 10.1074/jbc.m105398200
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Calcium in Stabilizing Transport Vesicle Coats

Abstract: Calcium has been implicated in regulating vesicle fusion reactions, but its potential role in regulating other aspects of protein transport, such as vesicle assembly, is largely unexplored. We find that treating cells with the membrane-permeable calcium chelator, 1,2-bis(2-aminophenoxy)ethane-N,N,N,N-tetraacetic acid tetrakis(acetoxymethyl ester) (BAPTA-AM), leads to a dramatic redistribution of the vesicle coat protein, coatomer, in the cell. We have used the cell-free reconstitution of coatprotomer I (COPI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 40 publications
0
63
0
Order By: Relevance
“…We found that treating cells with the membrane-permeable calcium chelator BAPTA-AM led to the dissociation of the COPI vesicle coat protein, coatomer, from the Golgi apparatus (31). Using cell-free Golgi binding assays, we also observed that the addition of BAPTA led to the rapid dissociation of coatomer from previously coated Golgi membranes.…”
mentioning
confidence: 57%
“…We found that treating cells with the membrane-permeable calcium chelator BAPTA-AM led to the dissociation of the COPI vesicle coat protein, coatomer, from the Golgi apparatus (31). Using cell-free Golgi binding assays, we also observed that the addition of BAPTA led to the rapid dissociation of coatomer from previously coated Golgi membranes.…”
mentioning
confidence: 57%
“…Accordingly, the addition of CaCl 2 suppresses the vacuole fragmentation phenotype of pmr1⌬ mutants (33). In addition, calcium might also regulate the formation of intraGolgi retrograde transport vesicles as it has been shown to stabilize COPI coat onto the Golgi membrane (67). The addition of CaCl 2 caused a significant increase in the intracellular calcium levels and might account for a permanent induction of retroand anterograde pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In higher eukaryotic cells, some of these processes, or steps thereof, are known to be subject to Ca 2ϩ regulation (1,6). In P. tetraurelia, all steps of exo-and endocytosis are known to be accelerated by increased [Ca 2ϩ ] (72), whereas no information is available on trichocyst biogen- esis.…”
Section: Discussionmentioning
confidence: 99%